2016
DOI: 10.1177/0898264316676406
|View full text |Cite
|
Sign up to set email alerts
|

Mild Visual Impairment and Its Impact on Self-Care Among Older Adults

Abstract: Objective: To determine the prevalence of mild visual impairment (MVI) among urban older adults in primary care settings, and ascertain whether MVI was a risk factor for inadequate performance on self-care health tasks. Methods: We used data from a cohort of 900 older adults recruited from primary care clinics. Self-management skills were assessed using the Comprehensive Health Activities Scale, and vision with corrective lenses was assessed with the Snellen. We modeled visual acuity predicting health task p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Functionally, the threshold of 0.5 in distance VA is relevant; as with current visual correction, it serves as the requirement for standard driving license in many states in the United States of America [41] and the countries of the European Union (directive 2006/126/EC), thereby affecting individual’s activities of daily living. Moreover, previous publication reports differences in self-care when VA is near the threshold of 0.5 (from 0.4 to 0.63) [42]. Our results point out that low vision correlates with low HRQoL.…”
Section: Discussionsupporting
confidence: 66%
“…Functionally, the threshold of 0.5 in distance VA is relevant; as with current visual correction, it serves as the requirement for standard driving license in many states in the United States of America [41] and the countries of the European Union (directive 2006/126/EC), thereby affecting individual’s activities of daily living. Moreover, previous publication reports differences in self-care when VA is near the threshold of 0.5 (from 0.4 to 0.63) [42]. Our results point out that low vision correlates with low HRQoL.…”
Section: Discussionsupporting
confidence: 66%
“…Lack of self-care behaviors and presence of depression are common among older adults. 11 , 40 , 41 Our study found that depression was prevalent before the intervention. After the intervention, depression was reduced at both follow-ups.…”
Section: Discussionmentioning
confidence: 54%
“…Falls among visually impaired adults can occur due to multifaceted intrinsic and extrinsic factors. In LMICs people with visual impairment are confronting a different set of challenges like accessibility barriers, navigator barriers, unemployment, health care utility challenges, and societal stigma [16,17]. Though, population-based studies had reported that old age and related-poor vision as a frequent risk factor for fall, yet the knowledge about visual-related clinical characteristics in falls among adults living in LMICs is sparse.…”
Section: Introductionmentioning
confidence: 99%